Total Factor Productivity in the Manufacturing Sector of Peru: 2002-2007 - Tello, Mario D. (2012)
Based upon manufacturing sector data, this paper estimates the total factor productivity (TFP) for this sector with parametric and modern methods for the 2002-2007 period. Subject to data limitations and methods used, the estimations indicate that the TFP growth rate for a representative sample of up to 578 firms was low in the period analysed, without having contributed to the growth of manufacturing firms’ real production value. In addition, the TFP growth rate was greater for large firms (more than 100 employees) than for medium and small firms (less than 21 employees). In terms of industrial sectors, TFP growth rates were higher for primary processing and technology-intensive industries than for traditional industries (such as textiles, clothing and footwear), and the foodstuffs, tobacco, and beverages sectors. Lastly, though capital, employmentand installed capacity growth may explain the growth of manufacturing real output value for the period 2002-2007, the absence of TFP growth may jeopardize the sustainability of such a growth in the medium and long run.